2019
DOI: 10.1101/725507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Integrator complex terminates promoter-proximal transcription at protein-coding genes

Abstract: Highlights:• The Integrator complex inhibits transcription elongation at ~15% of mRNA genes• Integrator targets promoter-proximally paused Pol II for termination• The RNA endonuclease of Integrator subunit 11 is critical for gene attenuation • Integrator-repressed genes are enriched in signaling and growth-responsive pathways SUMMARY The transition of RNA polymerase II (Pol II) from initiation to productive elongation is a central, regulated step in metazoan gene expression. At many genes, Pol II pauses stably… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Our analysis of protein-coding genes argues that this phenomenon is not just restricted to loci producing cryptic transcripts. Moreover, it suggests that TSS-proximal termination events may extend well beyond previously reported examples (Elrod et al, 2019;Iasillo et al, 2017;Kamieniarz-Gdula et al, 2019;Ogami et al, 2017;Tatomer et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Our analysis of protein-coding genes argues that this phenomenon is not just restricted to loci producing cryptic transcripts. Moreover, it suggests that TSS-proximal termination events may extend well beyond previously reported examples (Elrod et al, 2019;Iasillo et al, 2017;Kamieniarz-Gdula et al, 2019;Ogami et al, 2017;Tatomer et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Integrator interacts with the CTD of RNA Pol II and processes newly transcribed RNA molecules, mainly nonpolyadenylated transcripts and UsnRNAs. Integrator has also been recently implicated in the modulation of gene expression via regulation of protein-coding gene transcription initiation and premature termination (7,27), in RNA Pol II pause release (31,32), and in the biogenesis of enhancer RNAs (6). Here, we provide functional evidence for an unexpected role of Integrator in the regulation of the isoform switching of the lncRNA NEAT1.…”
Section: Discussionmentioning
confidence: 69%
“…(H) Western blot analysis for p53, p21, and phospho-H2AX, confirming the efficacy of the treatments; GAPDH is a loading control. (7,27), in RNA Pol II pause release (31,32), and in the biogenesis of enhancer RNAs (6). Here, we provide functional evidence for an unexpected role of Integrator in the regulation of the isoform switching of the lncRNA NEAT1.…”
Section: Discussionmentioning
confidence: 70%
“…A recent study by Nathan D. Elrod et al showed that Integrator can actively destabilize paused Pol II at the mRNA of coding genes as well. Similarly, Integrator utilizes its RNA endonuclease activity to cleave nascent RNA and drive the termination of paused Pol II [115]. Taken together, these findings reveal a previously unappreciated mechanism of transcription suppression inherent to promoters and enhancers alike.…”
Section: Pol II Pausing At Enhancersmentioning
confidence: 81%